Selective nuclear export of mRNAs is promoted by DRBD18 in Trypanosoma brucei - Mishra, Amartya; Kaur, Jan Naseer; McSkimming, Daniel I; Hegedűsová, Eva; Dubey, Ashutosh P; Ciganda, Martin; Paris, Zdeněk; Read, Laurie K (Molecular microbiology, 2021)
Kinetoplastids, including Trypanosoma brucei, control gene expression primarily at the posttranscriptional level. Nuclear mRNA export is an important, but understudied, step in this process. The general heterodimeric export factors, Mex67/Mtr2, function in the export of mRNAs and tRNAs in T. brucei, but RNA binding proteins (RBPs) that regulate export processes by controlling the dynamics of Mex67/Mtr2 ribonucleoprotein formation or transport have not been identified. Here, we report that DRBD18, an essential and abundant T. brucei RBP, associates with Mex67/Mtr2 in vivo, likely through its direct interaction with Mtr2. DRBD18 downregulation results in partial accumulation of poly(A)+ mRNA in the nucleus, but has no effect on the localization of intron-containing or mature tRNAs. Comprehensive analysis of transcriptomes from whole-cell and cytosol in DRBD18 knockdown parasites demonstrates that depletion of DRBD18 leads to impairment of nuclear export of a subset of mRNAs. CLIP experiments reveal the association of DRBD18 with several of these mRNAs. Moreover, DRBD18 knockdown leads to a partial accumulation of the Mex67/Mtr2 export receptors in the nucleus. Taken together, the current study supports a model in which DRBD18 regulates the selective nuclear export of mRNAs by promoting the mobilization of export competent mRNPs to the cytosol through the nuclear pore complex.
Keywords: Nucleocytoplasmic Transport Proteins; messenger RNA; RNA transferová; Membrane Transport Proteins; Protein Binding; transkriptom; nukleocytoplazmatické transportní proteiny; Gene Expression Regulation; aktivní transport - buněčné jádro; RNAseq; RNA-Binding Proteins; protozoální proteiny; RNA, Transfer; Transcriptome; Gene Knockdown Techniques; membránové transportní proteiny; regulace genové exprese; FISH; RNA, Messenger; mRNA export; Protozoan Proteins; Active Transport, Cell Nucleus; Trypanosoma brucei brucei; proteiny vázající RNA; RNA Transport; vazba proteinů; genový knockdown; nucleoporin; transport RNA; trypanosome; RNA binding protein